Production of Lipids from Municipal Sewage Sludge by Two Stage Extraction Process - Bharathi P; Pennarsi M (ASEAN Journal of Chemical Engineering, 2016)
In this investigation, municipal sewage sludge was used as a lipid feedstock. Two stage extraction processes was developed to obtain good yield of lipid content. The maximum lipid yields 32.5% was achieved from chloroform: methanol solvents through optimum conditions of 2:1 ratio, 50oC temp for 30 min. The lipid content was characterized by TLC analysis. The lipid properties were analyzed and proved as a lipid. Hence, municipal sewage sludge serves as a valuable raw material for lipid production